Comparison of oral midazolam with a combination of oral midazolam and nitrous oxide-oxygen inhalation in the effectiveness of dental sedation for young children - Al-Zahrani A; Wyne A; Sheta S (Wolters Kluwer Medknow Publications, 2009)
Aim: To compare the effectiveness of 0.6 mg/kg oral midazolam sedation alone and a combination of 0.6 mg/kg oral midazolam plus nitrous oxide-oxygen inhalation sedation, in controlling the behavior of uncooperative children during dental treatment. Study Design: The study had a crossover design where the same patient received two different sedation regimens, that is, oral midazolam 0.6 mg/kg and oral midazolam 0.6 mg/kg with nitrous oxide-oxygen inhalation during two dental treatment visits. Materials and Methods: Thirty children (17 males and 13 females) were randomly selected for the study, with a mean age of 55.07 (± 9.29) months, ranging from 48 - 72 months. A scoring system suggested by Houpt et al. (1985) was utilized for assessment of the children′s behavior. Results : There was no significant (p > 0.05) difference in the overall behavior assessment between the two sedation regimens, that is, oral midazolam alone and oral midazolam plus nitrous oxide-oxygen. However, the combination of midazolam and nitrous oxide-oxygen showed significantly (p < 0.05) superior results as compared to midazolam alone, in terms of controlling movement and crying during local anesthesia administration and restorative procedures. Conclusion: Compared to oral midazolam alone, a combination of oral midazolam and nitrous oxide inhalation sedation appears to provide more comfort to pediatric dental patients and operators during critical stages of dental treatment.